FREQUENCY DISTRIBUTION OF WIND SPEED OF QUETTA, PAKISTAN - Ilyas, Syed Zafar; Nasir, S. M.; Badshah, Taleem (Journal of Research (Science), 2025)
Wind data of twelve years have been analyzed for Quetta, Pakistan to produce the probability distributions. Data for Quetta station is recorded on hourly basis and converted into m s-1. Distributions are considered on monthly and annual basis: final results are compared and show 70-80% probability of hourly wind speed greater than 2.0 m s-1. The probability for occurrence of wind speedat any location in Quetta will help designing the diverse engineering parameters for wind turbines like Darrius or Savonius such as angle of attack on rotors, suitable gear system to make wind machines work even in clean spells, generators, length of rotors; cut-in, cut-out and rated wind speeds of rotors.